Crop producers’ technical efficiency and its determinants in Gurage zone, Ethiopia: A comparative analysis using rural-urban migration as a parameter - Mesfin Agza (Taylor & Francis Group, 2021)
In this study the technical efficiency of crop-producing households and the factors that influence it are explored, and comparisons are made using rural–urban migration as a comparative measure, in Gurage Zone, Ethiopia. The data were collected from 384 arbitrary picked rural households and analyzed using a stochastic frontier approach. Non-migrant households, migrant-sending households, and total samples had mean technical efficiency of 45.5%, 72.3%, and 57.4%, respectively, according to the findings. The household head’s age and distance from a neighboring town have a downbeat impact on technical inefficiency, whereas schooling, soil infertility, migratory experience, and distance to a nearby market have an upbeat upshot. With the diversified and specific solutions provided, the study is recommended the government body to focus on making the best use of available agricultural inputs, boosting soil fertility, and regulating the sources of technological inefficiency.